Residential Field Site Training Programme Abstracts: 48th Batch, Session: 2005-2006, 4th year MBBS Students, CMC - Editor, The (Journal of Chittagong Medical College Teachers’ Association, 2011)
DOI: 10.3329/jcmcta.v21i1.7687 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):83-86